Ovarian luteal category at the time of exogenous progesterone treatment alters pre-ovulatory follicle size and pregnancy outcome but not initial GnRH treatment in repeat-breeder crossbred dairy heifers submitted to the 7-day fixed-time AI protocol. (September 2022) - Chaikol, Warunya; Yadmak, Chayanon; Yama, Punnawut; Jitjumnong, Jakree; Sangkate, Molarat; U-krit, Warittha; Promsao, Nalinthip; Suriard, Assawadet; Mektrirat, Raktham; Panatuk, Julakorn; Van Doan, Hien; Wang, Chien-Kai; et al.
Highlights: Ovarian and fertility outcomes were similar for repeat-breeder crossbred dairy heifers with or without initial GnRH treatment. Presence of luteal tissue at the time of progesterone (P4) treatment in infertile heifers resulted in a 68.6% pregnancy rate (PR). The likelihood of PR was higher in infertile heifers bearing luteal tissue on the day of exogenous P4 trigger. Abstract: Repeat breeding is a substantial problem in heifer and cow breeding leading to greater infertility for female dairy herds. The aim of present study was to investigate the impact of corpus luteum (CL) presence and category and the first gonadotropin-releasing hormone (GnRH) administration concurrent with exogenous progesterone (P4) treatment on the largest follicle (LF) size and pregnancy rate (PR) in repeat-breeder crossbred dairy heifers submitted to the fixed-time artificial insemination (AI) protocol. Heifers ( n = 243) were synchronised with (+GnRH) or without (–GnRH) first GnRH in the 7-day P4-GnRH-prostaglandin F2α-based programme. Each GnRH group was divided on presence of CL into two groups (+CL and –CL) in a 2 × 2 factorial arrangement. The PR was similar among –GnRH–CL (20.7%), –GnRH+CL (68.8%), +GnRH–CL (30.4%), and +GnRH+CL (68.3%) groups. However, presence of CL in heifers produced a 43.6% increase in PR compared to PR of heifers without CL (odds ratio = 6.550). Heifers bearing large-sized CL had greater large-sized LF on the day of fixed-time AI and PR. Plasma P4 concentration was positively related with CL diameter ( r = 0.845; p  < 0.001). The diameter of ovarian LF on the day of fixed-time AI was positively associated with P4 concentrations ( r = 0.512; p  < 0.001). We highlight that ovarian CL presence and category at the time of exogenous P4 treatment alters pre-ovulatory follicle size and PR but not initial GnRH treatment in repeat-breeder crossbred dairy heifers submitted to service with the 7-day fixed-time AI programme.